Strategi Memenangkan Persaingan Bisnis Era Industri 4.0 - Anatan, Lina (Universitas Nusantara PGRI Kediri, 2022)
The industrial revolution 4.0 has a significant influence both on business actors in various industries and society in general. A seminar on business strategy in the era of the industrial revolution 4.0 was conducted as a means of sharing knowledge between academics and business. The seminar was attended by approximately thirty participants each of their sessions who are business engaged in various industrial fields in Bandung. The seminar was divided into three topics which included discussion of the history of the development of the industrial revolution, Indonesia's strategy in responding to the Industrial Revolution 4.0, and business strategies that could be implemented by business actors in responding to the Industrial Revolution 4.0. The event ended with a question and answer session, sharing business experiences between business, and national service. One thing that can be underlined is that if you want to be able to survive and win the competition, it is inevitable that business people must be able to adapt to changes that occur through the mastery of information and communication technology in all aspects of the business they have.